An Analysis of Figurative Language Used in Raditya Dika Novel Entitled “Koala Kumal” - Gebrina Samira; Bukhari Daud; Nurul Inayah (Universitas Syiah Kuala, 2022)
The purpose of this research was to find out types of figurative language used in the Koala Kumal novel. This study was conducted by using the framework from Kennedy (2011). This research used a qualitative method to describe and analyze the types of figurative language in Koala Kuma novel. The result shows that there were 72 sentences that have figurative language in Koala Kumal novel. From all the sentences, they were 30 expressions (42%) of hyperbole, 26 expressions (36%) of simile, 8 expressions (11%) of metaphor, 5 expressions or (7%) of personification, and 1 expression (1%) of metonymy, irony, and paradox. It indicated that the highest frequency of figurative language type in this novel is hyperbole. The author used hyperbole in this novel to make an exaggeration in his conversation. The use of hyperboles can create an atmosphere of humor in the Koala Kumal novel.